Pharmacological activities and molecular mechanisms of Pulsatilla saponins - Jinmiao Zhong; Lihua Tan; Meiwan Chen; Chengwei He (BMC, 2022)
Abstract Saponins are found in a variety of higher plants and display a wide range of pharmacological activities, including expectorant, anti-inflammatory, vasoprotective and antimicrobial properties. Pulsatilla chinensis (P. chinensis, Bai Tou Weng, 白頭翁) has been used medically in China for thousands of years for the treatment of diseases caused by bacteria, and it is rich in triterpenoid saponins. In recent decades, anemoside B4 (Pulchinenoside C) is well studied since it has been used as a quality control marker for P. chinensis. At the same time, more and more other active compounds were found in the genus of Pulsatilla. In this review, we summarize the pharmacological activities of Pulsatilla saponins (PS) and discuss the cellular or molecular mechanisms that mediate their multiple activities, such as inducing cancer cell apoptosis, inhibiting tumor angiogenesis, and protecting organs via anti-inflammatory and antioxidant measures. We aim to provide comprehensive analysis and summary of research progress and future prospects in this field to facilitate further study and drug discovery of PS.